Impact of Immunogenetic IL28B Polymorphism on Natural Outcome of HCV Infection. (26th February 2014) - De Re, Valli; Gragnani, Laura; Fognani, Elisa; Piluso, Alessia; Izzo, Francesco; Mangia, Alessandra; Crovatto, Marina; Gava, Graziella; Casarin, Pietro; Sansonno, Domenico; Racanelli, Vito; De Vita, Salvatore; et al.
Abstract : With the aim of investigating whether interleukin 28B gene (IL28B) rs1297860 polymorphism is associated with different hepatitis C (HCV) infection statuses, we compared IL28B allelic distribution in an Italian case series of 1050 patients with chronic infection and different outcomes, 47 individuals who spontaneously cleared HCV, and 178 blood donors. Furthermore, we compared IL28B variants among 3882 Caucasian patients with chronic infection, 397 with spontaneous clearance, and 1366 blood donors reported in PubMed. Overall data confirmed a relation between IL28B C allele and HCV spontaneous clearance. Furthermore, we found that IL28B T allele had a weak relation with chronic HCV progression to hepatocellular carcinoma. Study findings are in accordance with the hepatocellular carcinogenic model where IL28B TT genotype, by promoting a persistent chronic hepatitis which leads to both hepatocyte injury and chronic inflammation, could facilitate HCC development. Conversely, patients with lymphoproliferative disorders had not any significantly different IL28B rs1297860 allelic distribution than those with chronic HCV, but, like all chronic HCV-related diseases, they showed a lower CC frequency than patients who spontaneously cleared HCV. Study results confirmed the model of persistent HCV infection as a risk factor for the pathogenesis of both liver and lymphoproliferative disorders.